In Vivo Reductionist Approach Identifies miR-15a Protecting Mice From Obesity - Murgia, Nicola; Ma, Yuan; Najam, Syeda Sadia; Liu, Yu; Przybys, Joanna; Guo, Chenkai; Konopka, Witold; Vinnikov, Ilya A. (Frontiers in Endocrinology, 2022)
Obesity is a growing medical and social problem worldwide. The control of energy homeostasis in the brain is achieved by various regions including the arcuate hypothalamic nucleus (ARH). The latter comprises a number of neuronal populations including the first order metabolic neurons, appetite-stimulating agouti-related peptide (AgRP) neurons and appetite-suppressing proopiomelanocortin (Pomc) neurons. Using an in vivo reductionist approach and PomcCre-dependent CRISPR-Cas9, we demonstrate that miR-15a-5p protects from obesity. Moreover, we have identified Bace1, a gene previously linked to energy metabolism imbalance, as a direct target of miR-15a-5p. This work warrants further investigations of non-coding RNA-mediated regulation of energy homeostasis and might contribute to the development of novel therapeutic approaches to treat metabolic diseases.